Primary renal histiocytic sarcoma in a dog. Issue 3 (11th April 2022) - Pitt, Kathryn; Tremolada, Giovanni
Abstract: A 5‐year‐old, male, neutered, Australian Shepherd mix was presented for evaluation of a left renal mass diagnosed by the primary veterinarian. The dog had a 2‐month history of lethargy, vomiting and hyporexia. Abdominal ultrasound confirmed the presence of a large (9.9 cm [L] × 7.8 cm [H] × 10.7 cm [W]) renal mass involving the entire left kidney causing severe hydronephrosis. A ureteronephrectomy was performed. Histopathology was consistent with renal histiocytic sarcoma. Adjuvant chemotherapy with cyclohexylchloroethylnitrosurea (62 mg/m 2 every 3 weeks for five treatments) was initiated. The dog had progressive disease upon restaging at the time of the third dose. Single‐agent doxorubicin (25 mg/m 2 every 2 weeks for five treatments) was started as a rescue protocol but discontinued after one dose due to side effects. The dog was euthanased 185 days after surgery.